TRABAJAR EN LAS START-UP. Invertir y divertirse en empresas innovadoras - Marty, Olivier (2002)
The internet revolution of the last ten decades gave birth to a new economy and a new category of companies: the start-ups. We will focus on French start-ups and develop the analysis of their financial process, the specific culture and way of work in them and their global organisation.